Advances in Computer Science for Engineering and Education II - Hu, Zhengbing; Petoukhov, Sergey; Dychka, Ivan; He, Matthew (Advances in Intelligent Systems and Computing, 2020)
XVI, 671 p. 281 illus., 165 illus. in color.